Exergy Replacement Cost of Mineral Resources - Valero, Alicia; Valero, Antonio; Domínguez, Adriana (Journal of Environmental Accounting and Management, 2026)
This paper appraises the energy requirements for mineral production through an exergy approach taking into account the long-term decline in ore grades. In this context, the exergy replacement costs are defined as the exergy required for restoring mineral resources from a complete dispersed state where no deposits exist into the same conditions in which they were delivered by the ecosystems with the available technology. The exergy replacement cost is the point of reference in order to evaluate in a single variable, characteristics such as composition, concentration (ore grade) and the state of technology of mineral resources. With empirical data of energy requirements in mining as a function of the ore grade, the exergy replacement costs of cobalt, copper, gold, nickel and uranium are obtained. Additionally, a general expression of mining energy vs. ore grade is derived for those mineral commodities where no empirical data is available.